Mt. Etna Tilt Signals Associated with February 6, 2023, M=7.8 and M=7.5 Turkey Earthquakes - Laura Privitera; Ferruccio Ferrari; Angelo Ferro; Salvatore Gambino (International Journal of Geophysics)
On February 6, 2023, at 01 : 17 UTC, a M=7.8 earthquake struck the southern area of Turkey near Gaziantep town and was followed by a second earthquake of M=7.5 at 10 : 24 UTC with the epicenter in Elbistan city. Both events were associated with the Anatolian Fault System and have claimed over 50,000 victims, as reported by the Disaster and Emergency Management Authority, and caused serious damage in the regions of southern Turkey and northern Syria. Seismic waves related to strong Turkey earthquakes have been recorded both by seismic stations throughout the globe and on other devices such as the ground deformation (GNSS, strainmeters, or tiltmeters) networks. In this paper, we show and analyze the earthquake signals recorded by bore-hole tilt stations that monitor seismic and volcanic activities at Mt. Etna. Tilt stations showed very large variations, despite their distance from the epicenter (approximately 1950 km) with a period between 10 and 25 seconds. We compared tilt and seismic data for a co–located station evidencing a very similar waveform that highlight how tiltmeters respond to translational acceleration rather than ground tilt during a teleseism, suggesting that, for waves with this period, they may behave as horizontal seismometers. By using these signals, we evidence the different behaviors of two of the most used models of tiltmeters on volcanoes (Lily and Pinnacle) and how they are useful for instrument calibration.